Does Body Memory Exist? A Review of Models, Approaches and Recent Findings Useful for Neurorehabilitation - Chiara Parma; Federica Doria; Aida Zulueta; Marilisa Boscarino; Luca Giani; Christian Lunetta; Eugenio Agostino Parati; Mario Picozzi; Davide Sattin (Brain Sciences, 2024)
Over the past twenty years, scientific research on body representations has grown significantly, with Body Memory (BM) emerging as a prominent area of interest in neurorehabilitation. Compared to other body representations, BM stands out as one of the most obscure due to the multifaceted nature of the concept of “memory” itself, which includes various aspects (such as implicit vs. explicit, conscious vs. unconscious). The concept of body memory originates from the field of phenomenology and has been developed by research groups studying embodied cognition. In this narrative review, we aim to present compelling evidence from recent studies that explore various definitions and explanatory models of BM. Additionally, we will provide a comprehensive overview of the empirical settings used to examine BM. The results can be categorized into two main areas: (i) how the body influences our memories, and (ii) how memories, in their broadest sense, could generate and/or influence metarepresentations—the ability to reflect on or make inferences about one’s own cognitive representations or those of others. We present studies that emphasize the significance of BM in experimental settings involving patients with neurological and psychiatric disorders, ultimately analyzing these findings from an ontogenic perspective.